UNACCUSATIVE AND UNERGATIVE VERB VARIATION IN OVERPASSIVIZATION ERRORS: EXAMINING SPLIT INTRANSITIVITY HIERARCHY - Lin, Yowyu (Taiwan Journal of Linguistics, 2023)
One of the most well-known errors in second language acquisition is overpassivization of intransitive verbs. Even though many theories have been proposed to explain the nature of second language (L2) acquisition, very few can explain the huge verb variation found in these studies. Sorace's Split Intransitivity Hierarchy was originally proposed to explain native speakers' auxiliary selection across unaccusative and unergative verbs. Verbs in the hierarchy are classified into ＂Core,＂ ＂Less Core＂ and ＂Periphery＂ groups. Recently, this theory has been extended to explain L2 learners' acquisition of intransitive verbs. The current study re-examined overpassivization errors among L2 Mandarin learners with three different proficiency levels by looking at whether the error numbers they produced conform to the predictions of Sorace's Split Intransitivity Hierarchy and Perlmutter's Unaccusative Hypothesis. Participants were asked to describe pictures using target intransitive verbs, including both unaccusative and unergative verbs. The results were in support of Sorace's hypothesis. Subjects produced significantly more errors in ＂Periphery＂ and ＂Less Core＂ categories than in the ＂Core＂ category. In addition, the results of the experiment also supported the Unaccusative Hypothesis.